PENGALAMAN AWAL DAPAT MENGUBAH EKSPRESI GEN DAN MEMPENGARUHI PERKEMBANGAN JANGKA PANJANG - Farah Ayu Maulidina; Debbie Susanti; Siti Kania (incrementapedia, 2022)
New scientific research shows that environmental influences can actually affect whether and how genes are expressed. Thus, the old idea that genes are "set in stone" or that they alone determine development has been debunked. In fact, scientists have found that early experiences can determine how genes are turned on and off and even whether some are expressed at all. Therefore, the experiences that children have early in life and the environment in which they have them are able to shape the structure of their developing brains and greatly influence whether they grow up to be healthy and productive members of society. This growing body of scientific evidence supports the need for society to re-examine the way it thinks about the circumstances and experiences to which young children are exposed.